Prevalence and determinants of under-nutrition among children on ART in Ethiopia: A systematic review and meta-analysis - Gelaw Walle, Belete; Selomon, Nigusie; Tiruneh, Chalie Marew; Chekole, Bogale; Kassaw, Amare; Wubneh, Moges; Assefa, Yibeltal; Abebe, Kelemu (PloS one, 2024)
Children living with HIV/AIDS are particularly vulnerable to under-nutrition. Under-nutrition associated with HIV/AIDS infection increases the rate of morbidity and mortality in children. To reaffirm a future objective, there needs to be evidence regarding the current national burden of under-nutrition and related factors among children infected with HIV. Hence, the objective of this systematic review and meta-analysis was to estimate the pooled prevalence of under-nutrition, and the pooled effect sizes of associated factors among HIV-infected children in Ethiopia. We searched Ethiopian universities' online libraries, Google, Google Scholar, PubMed, CINAHL, Cochrane Library, and Scopus to find the primary studies for this review. Publication bias was checked through Egger's regression test. Heterogeneity among the included studies was assessed using the I2 test. The data were extracted using Microsoft Excel and exported to STATA Version 14 statistical software. A random effect meta-analysis model was performed to estimate the pooled prevalence of Under-nutrition. After reviewing 1449 primary studies, 16 articles met the inclusion criteria and were included in the final meta-analysis. The estimated pooled prevalence of stunting, underweight, and wasting among children living with HIV/AIDS was 32.98% (95% CI: 22.47, 43.50), 29.76% (95% CI: 21.87, 37.66), and 21.16% (95% CI: 14.96, 27.35) respectively. This study showed that under-nutrition among HIV-infected children in Ethiopia was significantly high. Under-nutrition is more common among HIV-infected children with opportunistic infections, child feeding problems, do not adhere to dietary recommendations, and have diarrhea. The national policies and strategies for ART service- provider centers should maximize their emphasis on reducing under-nutrition among HIV-infected children. Based on this finding, we recommend HIV intervention programs to address nutritional assessment and interventions for HIV-infected children. The protocol has been registered in the PROSPERO database with a registration number of CRD-394170.